2014
DOI: 10.15403/jgld.2014.1121.233.arom1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells Count Predicts Survival in Colorectal Cancer Patients

Abstract: Background & Aims: Data on the potential of circulating tumor cells (CTC) count in predicting overall survival (OS) in patients with colorectal cancer are timely and worthy of interest. This study aimed to evaluate the prognostic role of CTC count in both localized and metastatic colorectal cancer patients.Methods: Consecutive patients with histological diagnosis of colorectal cancer were enrolled. CTC count was performed, by using a quantitative immunofluorescence method, at baseline (T0) and 1 month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…However, besides this, our results were similar to a recently published study that demonstrates a correlation of CTC kinetics in metastatic breast cancer (mBC) with prognosis and evaluation of response to the treatment adopted 39. This study with 356 mBC patients demonstrated that those with favorable CTC kinetics had a higher propensity to respond to the proposed treatment, supporting the evaluation that the dynamic counting of CTCs could better reflect the prognosis and the aggressiveness of the disease than the isolated counting of cells 37. Cohen et al28,40 in their publications on mCRC using CellSearch ® System also demonstrated the importance of CTC kinetics with evidence of increased survival for patients with conversion from unfavorable to favorable CTC condition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, besides this, our results were similar to a recently published study that demonstrates a correlation of CTC kinetics in metastatic breast cancer (mBC) with prognosis and evaluation of response to the treatment adopted 39. This study with 356 mBC patients demonstrated that those with favorable CTC kinetics had a higher propensity to respond to the proposed treatment, supporting the evaluation that the dynamic counting of CTCs could better reflect the prognosis and the aggressiveness of the disease than the isolated counting of cells 37. Cohen et al28,40 in their publications on mCRC using CellSearch ® System also demonstrated the importance of CTC kinetics with evidence of increased survival for patients with conversion from unfavorable to favorable CTC condition.…”
Section: Discussionsupporting
confidence: 91%
“…Defining the initial treatment with one, two, or three medications associated or not with biological agents (monoclonal antibodies and tyrosine kinase inhibitors) becomes more difficult due to clinical and pathological complexities of mCRC and the lack of non-radiological markers that are useful for defining therapeutic strategies. In this way, evaluating the dynamics of CTCs could guide the oncologists in choosing a systemic therapy and predicting the clinical response from favorable and unfavorable patients 37,38…”
Section: Discussionmentioning
confidence: 99%
“…However, technological shortcomings and difficulty in finding the perfect markers to identify such CTCs or ctDNA have resulted in few studies of any clinically valuable difference in terms of survival outcomes or prediction[31]. Other studies appear promising, including one recent meta-analysis on the prognostic role of ctDNA[32], also for disease prediction but are small and need further validation[33-35]. …”
Section: Liquid Biopsies: Circulating Tumor Cells and Circulating Tummentioning
confidence: 99%
“…Therefore, to seek a sensitive method in the detection of potential meningeal metastasis is extremely necessary. Previous studies have identified that blood circulating tumor cells (CTCs), namely solid tumor cells falling into the blood, have a high correlation with tumor diagnosis (3), metastasis and prognosis (4,5). In the present study, CTCs in the cerebrospinal fluid (CSF) of patients with meningeal metastasis from lung cancer were detected using immunofluorescence in situ hybridization (immuno-FISH) technology and the detection value of the CTCs were evaluated in the adjuvant diagnosis of meningeal metastasis from lung cancer.…”
Section: Introductionmentioning
confidence: 99%